Application of the CERT values measurement model for organizational culture in the Management And Quality company (2023)
At present, it has been shown that very few SMEs have knowledge of the Business Process Management BPM system, which offers a series of strategies and benefits oriented towards processes, using technology systems in terms of information management, evaluating the organizational culture and covering all the operational and business processes of the organization, in order to increase productivity and competi tiveness, guaranteeing continuous improvement of internal processes following their life cycle, where they are documented, analyzed, improved , are implemented, and are monitored and controlled. In this study, the BPM culture of an information technology SME, called Man agement and Quality, was evaluated based on the study carried out by Jan Vom Brocke, in which 4 values are established, which are: customer orientation, excel lence, responsibility, and teamwork, called CERT values, the survey adapted to the context of the company and Colombia was applied; As a result, opportunities for improvement in excellence were found represented by the dimensions of contin uous improvement and innovation, and in the formal structures, dimension of teamwork, recommendations were made for these findings.